Validation of the Obsessive-Compulsive Inventory Revised (OCI- R) for Spanish adolescent population - Martínez González, Agustín Ernesto; Piqueras, José Antonio; Marzo, Juan Carlos (Anales de Psicología / Annals of Psychology, 2011)
There is a growing interest in instruments designed to assess obsessive-compulsive symptoms in children and adolescents. The Obsessive Compulsive Inventory-Revised (OCI-R) has demonstrated to be a valid and useful test in the evaluation of these symptoms cross-culturally in both clinical and nonclinical settings. The aim of this study was to examine and extend the psychometric properties and factor structure of the OCI-R in a non-clinical sample of 525 adolescents (mean age=15.82; SD=1.77; range=12-18). The results confirmed the original six-factor structure of the OCI-R (Washing, Obsessing, Hoarding, Ordering, Checking and Neutralizing), as well as the internal consistency, temporary stability, and concurrent-discriminant validity. To sum up, the OCI-R is a short and reliable instrument that measures global as well as domain-specific obsessive-compulsive symptomatology in adolescence, what is consistent with previous literature. Whether it will retain its psychometric properties in clinical samples of adolescents remains to be investigated.